Ta có: bx−cyabx−cya = cx−axbcx−azb = ay−bxcay−bxc
⇒ bx−cyabx−cya = a(bx−cy)a²a(bx−cy)a² = abx−acya²abx-acya²
cx−azbcx−axb = b(cx−az)b²b(cx−az)b² = bcx−baxb²bcx−baxb²
ay−bxcay−bxc = c(ay−bx)c²c(ay−bx)c² = cay−cbxc²cay−cbxc²
Áp dụng tính chất dãy tỉ số bằng nhau, ta có:
bx−cyabx−cya = cx−azbcx−axb = cy−bxccy−bxc = abx−acy+bcx−bax+cay−cbxa²+b²+c²abx−acy+bcx−bax+cay−cbxa²+b²+c² = 0
\(\Rightarrow\) bx - cy = 0
cx - ax = 0
ay - bx = 0
\(\Rightarrow\) bx = cy
cx = ax
ay = bx
\(\Rightarrow\) xcxc = ybyb
xaxa = xcxc
ybyb = xaxa
\(\Rightarrow\) xaxa = ybyb = xcxc
cyabx o dau vay